A study of sexual dimorphism of human auricle by morphometry and topographical location - M Maitreyee (Wolters Kluwer Medknow Publications, 2018)
Aims and objectives: Features of human body parts or organs or bones have been studied to identify differences in males and females. The present study was performed to assess gender differences in morphometric parameters of auricle of ear; and to see whether there exists any sexual dimorphism in positioning of auricle. Materials and Methods: Measurements were taken on 350 young individuals within the age group of 17-25 years by digital and spreading calipers and recorded in centimeters. The morphometric parameters were auricle length, auricle width, auricle root/attachment, projection of auricle, face height, face width, position of auricle from anterior midline, and position of auricle from posterior midline. The independent t-test was used to test the significance of difference between males and females. Results: The difference in the morphometric parameters showed statistical significance. The indices i.e. 'Position of auricle from posterior midline' [PEP] to face width [FW] index was statistically significant sex-wise, which was less in males than in females; while 'Position of auricle from anterior midline' [PEA] to 'Position of auricle from posterior midline' [PEP] index was also statistically significant sex-wise, which was more in males than in females. Conclusion: There was significant difference in measurements as well as position of auricle in males and females. The two indices related to the position of auricle from the midline may be of value in forensic identification and in fields like surgery, anthropometry, art, and ergonomics. Corresponding landmarks on dry skull may be used to estimate sex in skeleton.